2014
DOI: 10.4028/www.scientific.net/amr.891-892.986
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Retardation in LSP and Sp Treated Aluminium Specimens

Abstract: Highly loaded aircraft components have to fulfill strict fatigue and damage tolerance requirements. For some components besides the crack initiation mainly the fatigue crack propagation behavior is the main design criteria. To improve the crack propagation behavior of a component several methods are known or have been described in literature. For thin aircraft panels i.e. the application of crenellations [1] or bonded doublers [2, 3] can be a solution. For thick structures mainly the introduction of compressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…LSP treatment has a strong beneficial effect on the fatigue performance of structural components because the compressive residual stress field induced in the material considerably retards fatigue crack growth 27–34 . Therefore, a significant improvement in the fatigue behaviour and lifetime prolongation can be achieved for components and structures with surface cracks 27,28,31,34 as well as through‐thickness cracks 29,30,32,33 . Lin et al have investigated the effect of LSP on the fatigue strength of engine components subjected to foreign object damage (FOD), where LSP is applied before FOD 35 .…”
Section: Introductionmentioning
confidence: 99%
“…LSP treatment has a strong beneficial effect on the fatigue performance of structural components because the compressive residual stress field induced in the material considerably retards fatigue crack growth 27–34 . Therefore, a significant improvement in the fatigue behaviour and lifetime prolongation can be achieved for components and structures with surface cracks 27,28,31,34 as well as through‐thickness cracks 29,30,32,33 . Lin et al have investigated the effect of LSP on the fatigue strength of engine components subjected to foreign object damage (FOD), where LSP is applied before FOD 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a significant improvement in the FCP behaviour was demonstrated by Hombergsmeier et al (2014) [8] in the case of AA2024T3 M(T) specimens with two LSPstripes outside the initial notch. The retardation effect of LSP on the FCP rate was attributed to high compressive residual stresses, which were generated in 2 mm-thick AA2024 sheets.…”
mentioning
confidence: 95%
“…LSP-induced residual stresses can be used to improve the damage tolerance behaviour of lightweight metallic structures. Several researches investigated the effects of LSP on the initiation and propagation of fatigue cracks in aluminium alloy specimens with various notch geometries [1,[5][6][7][8][9]. The results clearly demonstrated that LSP can be used as an effective surface treatment technique for reducing or suppressing fatigue crack growth in aluminium alloys.…”
Section: Introductionmentioning
confidence: 95%